ASSESSMENT NAMESPACE AIR POLLUTION AREASIN THE EVENT OF FAILURE OF THE MERCURY LIGHT SOURCES - Дмитруха, Т. І. (Science-based technologies, 2014)
Assessment of the existing status of atmosphere air in the case of destruction of the light sources containing mercury has been done. It is shown that the lamps, which have mercury in their structure, create considerable hazard of the mercury pollution for environment, living accommodations, child-care institutions, recreational premises etc. Assessment has been done regarding the change in concentration of mercury vapor in air of premises of different area in the case of destruction of the compact mercury-vapor lamp (2.5 mg of mercury) and the luminescent lamp (50 mg of mercury). It is shown that in the case of destruction of the compact as well as the luminescent mercury-vapor lamp in premises of different area staying of people in those premises even one hour after the incident will be dangerous. It is proved that the special demercurization measures should be done in the case of further staying of the staff in the premise after destruction of the lamp containing mercury within it in purpose to prevent serious harmful impact on their health.